Estimating the economic value of hydropeaking externalities in regulated rivers - Ruokamo, Enni; Juutinen, Artti; Ashraf, Faisal Bin; Haghighi, Ali Torabi; Hellsten, Seppo; Huuki, Hannu; Karhinen, Santtu; Kopsakangas-Savolainen, Maria; Marttila, Hannu; Pongracz, Eva; Romakkaniemi, Atso; Vermaat, Jan E. (Elsevier BV, 2024)
Hydropower is a flexible form of electricity generation providing both baseload and balancing power to accommodate intermittent renewables in the energy mix. However, hydropower also generates various externalities. This study investigates individuals' preferences for policies aiming to reduce short-term regulations (i.e., hydropeaking in regulated rivers) while accounting for associated externalities with a discrete choice experiment. This is the first valuation study focusing on hydropeaking that considers both negative and positive externalities. The results imply that most individuals prefer stronger restrictions on short-term regulations to mitigate local environmental impacts. Individuals especially value improvements in recreational use, fish stocks, and the ecological state. On the other hand, potential increases in CO2 emissions are linked with a clear disutility. The estimated benefits obtained from an improved state of the river environment due to such restrictions exceed the disutility caused by increased CO2 emissions. The results also reveal unobserved preference heterogeneity among individuals, which should be accounted for in the willingness-to-pay (WTP) estimation using a model specification with correlated utility coefficients. Overall, the findings can inform policy-makers and environmental managers on the economic value of hydropeaking externalities and further guide the sustainable management of rivers regulated for hydropower generation.
Keywords: Choice experiment; Correlation; Ecosystem service; Hydropower; Kemijoki